ARSHOGHNA (ANTI-HEMORRHOIDAL) HERBAL DRUGS OF RAJNIGHANTU: A LITERARY REVIEW - Biswal, Anshuman; Thakur, Deepika; Prabala, Varsha (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda plays vital role in curing Arsha (Hemorrhoids) without surgical intervention there are so many herbal drug having Arshoghna property. Many treatment modalities have been explained in Brihatrayi (Charak, Sushruta, Vagbhata) and Laghutrayi (Sharangdhara, Bhavaprakash and Madhav Nidan). In Rajnighantu pandit Narahari mentions numerous drugs acting on hemorrhoids. The present study is designed to screen the drugs with Arshoghna, Visheshat, Gudajapaham, Raktarshara, Gudaraktahruta, Gudankurnash, Gudartinash, Vatarshahara properties. Out of 789 herbal drugs 38 were described in for the treatment of hemorrhoids throughout the text of Rajnighantu.In Arshas management the systemic medicines act by improving appetite, regularize bowl habits, astringent action on blood vessels and maintaining Agni and Srotas in equilibrium. Among all the Arshoghna drugs are described in Rajnighantu, maximum drug are Tikta or Katu or Kasaya rasa Pradhana and most of the drug is Usna in Virya. It can also be said that the drugs having Katu, Tikta, Kashaya rasa, Guru, Tikshna and Ksharaguna, Ushnavirya and Katuvipaka play major role in the treatment of Arsha.